The Effect of Arctic Sea Ice Loss on the Hadley Circulation. Issue 2 (29th January 2019) - Chemke, R.; Polvani, L. M.; Deser, C.
Abstract: One of the most robust responses of the climate system to future greenhouse gas emissions is the melting of Arctic sea ice. It is thus essential to elucidate its impacts on other components of the climate system. Here we focus on the response of the annual mean Hadley cell (HC) to Arctic sea ice loss using a hierarchy of model configurations: atmosphere only, atmosphere coupled to a slab ocean, and atmosphere coupled to a full‐physics ocean. In response to Arctic sea ice loss, as projected by the end of the 21st century, the HC shows negligible changes in the absence of ocean‐atmosphere coupling. In contrast, by warming the Northern Hemisphere thermodynamic coupling weakens the HC and expands it northward. However, dynamic coupling acts to cool the Northern Hemisphere which cancels most of this weakening and narrows the HC, thus opposing its projected expansion in response to increasing greenhouse gases. Plain Language Summary: The climate's response to anthropogenic emissions comprises different feedbacks of the different components in the climate system. One of the robust responses to increased greenhouse gases is the melting of Arctic sea ice, which is found to have large effects on the hydrological circulation in the atmosphere. Here we examine the effect of Arctic sea ice loss on the tropical circulation. We find that under Arctic sea ice loss ocean heat transport acts to transfer the Arctic signal to the tropics and to contract the tropical circulation. This contraction opposes the projected widening of the tropical circulation and thus shows that Arctic sea ice loss acts as a negative internal feedback in the response of the tropical circulation to increased greenhouse gases. Key Points: Arctic sea ice loss affects the Hadley cell only through ocean‐atmosphere coupling Arctic sea ice loss acts as a negative internal feedback in the response of the Hadley cell width to anthropogenic emissions Ocean heat transport opposes the thermodynamic effect of Arctic sea ice loss on the Hadley circulation